Risky alcohol use and heavy episodic drinking among Spanish University students: a two-year follow-up Consumo de riesgo y consumo intensivo de alcohol entre estudiantes universitarios: dos años de estudio - Nayara Mota; Rosa Álvarez-Gil; Montserrat Corral; Socorro Rodríguez Holguín; María Parada; Alberto Crego; Francisco Caamaño-Isorna; Fernando Cadaveira (Elsevier, 2010)
Objective: To evaluate the incidence of risky consumption (RC) and heavy episodic drinking (HED) in the Cohort of Spanish university students at two-year follow-up and to identify predictors of these patterns of alcohol consumption and the association between these patterns and academic achievement. Method: We carried out a cohort study. Alcohol consumption was measured with the AUDIT. The following variables were collected by questionnaire: place of residence, parents' education, alcohol consumption in the family, age of onset of use, alcohol expectancies, and the academic achievement. We constructed logistic regression models using three dependent variables: RC, HED, and academic achievement. Results: The response rate at two-year follow-up was 64.1%. The incidence of RC and HED at two-year follow-up were 24.92% and 4.01% respectively. The prevalence of RC rose from 37.1% to 54.6%. On the contrary, HED dropped from 12.2% to 8.7%. In relation to incidence of RC, being male (OR=2.77), medium (OR=1.59) or high expectancies (OR=2.24), and early age of onset of use (OR=2.26) constituted risk factors. In contrast, living with parents constituted a protective factor (OR=0.48). For HED, being male (OR=1.92) and high expectancies (OR=2.96) were risk factors. RC and HED were risk factors for low academic achievement. Conclusions: HED is a pattern of alcohol consumption mainly associated with adolescence, while RC is associated with youth. Both patterns are predictors of academic achievement. Public Health strategies should focus on modifying expectancies and limit access to alcohol at young ages. Objetivo: Determinar la incidencia del consumo de riesgo de alcohol (CR) y del consumo intensivo (CI) en una cohorte de estudiantes universitarios a los 2 años de seguimiento e identificar los factores de estas pautas de consumo de alcohol y su asociación con el redimiento académico. Método: Se ha realizado un estudio de cohortes. El consumo de alcohol se ha medido con el AUDIT. Las siguientes variables se han medido mediante cuestionario: lugar de residencia, educación parental, consumo de alcohol en la familia, edad de inicio de uso, expectativas sobre alcohol y rendimiento académico. Para el análisis de datos se han construido modelos de regresión logística con las tres variables dependientes consideradas: CR, CI y rendimiento académico. Resultados: La tasa de respuesta en el seguimiento se situó en el 64,1%. La incidencia de CR y CI a los 2 años fue del 24,92% y el 4,01%. La prevalencia de CR aumentó del 37,1% al 54,6%. Por el contrario, el CI disminuyó del 12,2% al 8,7%. Con relación a la incidencia de CR, el ser varón (OR=2,77), las medias (OR=1.59) y altas expectativas (OR=2.24), y la edad temprana de inicio de uso (OR=2,26) son factores de riesgo. Por el contrario, el vivir con los padres muestra un factor protector (OR=0,48). Para el CI, ser varón (OR=1,92) y las altas expectativas (OR=2,96) son también factores de riesgo. Ambos patrones de consumo constituyen factores de riesgo del bajo rendimiento académico. Conclusiones: El CI es un patrón de consumo principalmente asociado con la adolescencia, mientras que el CR se asocia con la juventud. Ambos patrones son predictores del rendimiento académico. Las estrategias de salud pública deberían centrarse en la modificación de expectativas y en limitar el acceso al alcohol de los más jóvenes.